2017
DOI: 10.3823/2449
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women Positioning in Spinal Anesthesia for Cesarean Section: Integrative Review

Abstract: Objective: to analyze the scientific evidence on the positioning of pregnant women in spinal anesthesia for cesarean section.Method: an integrative review of the literature in the Scopus, CI-NAHL, LILACS and PubMed databases using the descriptors "patient positioning", "spinal anesthesia" and "obstetrics" and their synonyms "patient position" and "spinal anesthetics". Results:The sample of 8 articles showed that the fastest onset of blockade in pregnant women occurs in the lateral horizontal decubitus position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In terms of education, the majority of participants were below the tertiary level with a significant number never attending school. Meanwhile, Pinto et al (2017) demonstrated among a Brazilian population that education was a statistically significant factor to define patients who knew about anesthesia services and anesthetists. This may be explained by the relationship that those of higher intellect look for more information and show more coherent assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of education, the majority of participants were below the tertiary level with a significant number never attending school. Meanwhile, Pinto et al (2017) demonstrated among a Brazilian population that education was a statistically significant factor to define patients who knew about anesthesia services and anesthetists. This may be explained by the relationship that those of higher intellect look for more information and show more coherent assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an integrative review was performed which, despite the small number of articles published on the subject, showed that the positioning influences the effect, empowerment and time of onset, besides the pregnant woman's comfort and hemodynamic parameters, revealing its importance for the perioperative period and obstetric practice. (5) These findings reinforced the need to construct educational technology on the subject, whose elaboration should be evidence-based, so that it has valid and understandable content for the target audience and contributes effectively to obstetric clinical practice.…”
Section: Introductionmentioning
confidence: 88%
“…The bibliographic survey considered the literature on the subject, in addition to the findings from the integrative review mentioned earlier. (5) Based on the scientific evidence identified, the authors constructed the flipchart. The recommendations were followed for the writing and layout of text for educational technologies for people with low education levels.…”
Section: Bibliographic Survey and Construction Of Flipchartmentioning
confidence: 99%
“…Another factor that influences the spread of anesthesia is the position and baricity of local anesthesia 30 . Measures to avoid high spinal block are low dose local anesthesia 31 , adjusting the dose of bupivacaine according to the patients height 5,6 and BMI 8,31 , slow injection of local anesthesia 28 , administering local anesthesia in sitting position 32 and isobaric local anesthesia 30 .…”
Section: Risk Factorsmentioning
confidence: 99%